Advokasi dan Edukasi Masyarakat tentang Bahaya Rentenir Di Desa Sukatani Purwakarta - Sucipto, Moch. Cahyo (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The existence of moneylenders or by other names bank emok/mobile bank, is still a "ghost in broad daylight" for the community, besides being disturbing, its existence is often needed by people with minimal education levels about the dangers of borrowing and borrowing money in the style of moneylenders. The condition of urgent economic needs for the community makes moneylenders have the opportunity to run their business, namely lending money. The problem that arises when people are unable to pay off their debt payments is that they have to lose the assets they have. The purpose of this PKM is to provide understanding to the public, both those who have been ensnared and those who have not, to avoid loan sharks under the guise of a mobile bank. The results of PKM activities in the context of Advocacy and public education about the dangers of moneylenders in Sukatani village, Sukatani sub-district, Purwakarta district have been carried out well and smoothly. The targets of this PKM are community members and youth youth groups to be able to understand and be more aware of the dangers of the existence of loan sharks in the community, as well as build public awareness to be wiser in managing family finances and avoid debt habits, then remind the community to return revive the culture of mutual cooperation by providing assistance to people who face sudden needs such as medical treatment, house renovation and so on. Through this PKM activity, the community has understood the law of usury which is implemented in interest-bearing loans applied by moneylenders.